2002
DOI: 10.1055/s-2002-32723
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Hemodynamic Disturbances - Pathophysiological Background of Intestinal Motility Disturbances in Small for Gestational Age Infants

Abstract: Uteroplacental insufficiency leads to fetal growth retardation which is a major cause of perinatal and postnatal morbidity. In the present study we investigated the relationship between prenatal hemodynamic disturbances and postnatal intestinal perfusion and gastrointestinal function in small for gestational age neonates. Prospectively, 124 preterm neonates with a birth weight below 1500 g were assigned to one of two groups according to the prenatal Doppler sonographic measurements: neonates with or without pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 10 publications
(11 reference statements)
2
15
0
5
Order By: Relevance
“…Similar findings to our own were documented by Robel-Tillig et al ,10 who found a very high incidence of intestinal dysmotility and delayed feed tolerance in babies with abnormal antenatal umbilical artery pulsatility index. However, this was not found by Mihatsch et al 11 with similar fetal Doppler findings or by Adiotomre et al 12 following fetal absent end-diastolic flow in the umbilical artery.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings to our own were documented by Robel-Tillig et al ,10 who found a very high incidence of intestinal dysmotility and delayed feed tolerance in babies with abnormal antenatal umbilical artery pulsatility index. However, this was not found by Mihatsch et al 11 with similar fetal Doppler findings or by Adiotomre et al 12 following fetal absent end-diastolic flow in the umbilical artery.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, significant differences in the muscularis of the small intestine were shown (Table 2). Thinner muscularis, notably in the IUGR jejunum, compared to NBW piglets helps to explain altered motility of IUGR intestine [23]. …”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the relation between fetal blood flow pulsatility and gastrointestinal disturbances. [7][8][9][10][11][12] As enteral feeding may increase the risk of NEC, its initiation is often postponed. Minimal enteral feeding (MEF) has recently been introduced as a strategy to improve feeding tolerance and to prevent complications of prolonged parenteral nutrition, such as gut mucosa atrophy.…”
mentioning
confidence: 99%